2011
DOI: 10.1186/1471-2164-12-124
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of gene expression by alcohol exposure at early neurulation

Abstract: BackgroundWe have previously demonstrated that alcohol exposure at early neurulation induces growth retardation, neural tube abnormalities, and alteration of DNA methylation. To explore the global gene expression changes which may underline these developmental defects, microarray analyses were performed in a whole embryo mouse culture model that allows control over alcohol and embryonic variables.ResultAlcohol caused teratogenesis in brain, heart, forelimb, and optic vesicle; a subset of the embryos also showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 70 publications
(63 reference statements)
9
81
0
Order By: Relevance
“…Deformed organs included branchial arch, heart, neural tube, optic vesicle, otic vesicle, somite, and tail ( Fig. 1), which is in agreement with previous reports (Giavini et al, 1992;Zhou et al, 2011).…”
Section: Effects Of Ethanol On the Growth Of Cultured Rat Embryossupporting
confidence: 92%
“…Deformed organs included branchial arch, heart, neural tube, optic vesicle, otic vesicle, somite, and tail ( Fig. 1), which is in agreement with previous reports (Giavini et al, 1992;Zhou et al, 2011).…”
Section: Effects Of Ethanol On the Growth Of Cultured Rat Embryossupporting
confidence: 92%
“…28,52 In addition, experimental evidence has shown that embryonic alcohol exposure altered expression of genes that are specifically involved in the induction and development of the otic vesicle in zebrafish. For example, acute embryonic alcohol exposure reduces expression of the raldh2 gene that is required to activate retinoic acid signalling at the beginning of gastrulation.…”
Section: Inner Ear Damagementioning
confidence: 99%
“…Alcohol consumption in early pregnancy, and especially around gastrulation (third week) when pregnancy may be unknown, has been shown to lead to a high FAS incidence [6,13,14]. Inhibition of neural stem cell differentiation by ethanol in mouse has been proposed as the mechanism of developmental delay and deficits of the nervous system underlying FAS phenotypes [15,16]. An earlier ethanol perturbation of embryonic development at the stage of cell lineage specification [17] would impact formation of the ectoderm lineage and derived progenitors.…”
Section: Introductionmentioning
confidence: 99%